Особливості проектування процесу здоров’язберігального навчання студентів на засадах фундаменталізації змісту загальної фізкультурно-оздоровчої освіти - Завидівська, Наталія; Zavydivs’ka, Nataliia (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті обґрунтувано теоретико-методичні засади фундаменталізації фізкультурно-оздоровчої освіти в процесі здоров’язберігального навчання студентів вищих навчальних закладів різного професійного спрямування. Подано аналіз сучасного стану теоретичної розробки технологій і методик здоров’язбереження в системі фізичного виховання студентів із позиції фундаменталізації та розкрито її сутність. Представлено організаційно-педагогічні умови, принципи, змістовні блоки й етапи здоров’язберігального навчання та розкрито особливості організації процесу фізичного виховання студентів у компетентнісно орієнтованому форматі в умовах фундаменталізації фізкультурно-оздоровчої освіти. Розроблено й упроваджено в процес фізичного виховання авторську педагогічну здоров’язберігальну технологію навчання студентів. Доведено ефективність її використання у вищих начальних закладах різного професійного спрямування. The article is dedicated to the argumentation of theoretical and methodological basis of physical training fundamentalisation and students health-improving education in the process of health-preserving training. It is offered the analysis of nowadays situation in the process of technologies and methodologies theoretical developments of health-preserving in the system of physical training education of various professional directions institutions of high learning from the position of fundamentalisation and their essence is also developed. There are also offered the organizational and pedagogical conditions, principles and content blocks of students health-preserving training in the competence-oriented format under the condition of fundamentalisation of physical training education.The author pedagogical health-preserving technology of students training is developed and implemented in the process of physical training education. The effectiveness of its usage in the various professional directions institutions of high learning is proved. The implementation of new created pedagogical health-preserving training technology caused statistically correct improvement of students physical activity; knowledge improvement, abilities and skills; reduction of students absence in the case of sickness. Moreover, the improvement of morphofunctional indices, physical training activity level took place and their self-esteem of their own competence in the sphere of health-preserving, physical-training knowledge.
Planning Features of the Health Preser Vingteachingprocess of Students Through Fundamentalizatoin of the Contentof General Physical Training and Health-Improvement Education
Keywords: фундаменталізація; fundamentalisation; фізкультурно-оздоровча освіта; студенти; фізичне виховання; вищі начальні заклади різного професійного спрямування; педагогічна здоров’язберігальна технологія навчання; health-improving education; students; physical-training education; various professional directions institutions of high learning; pedagogical health-preserving training technology